2022
DOI: 10.1038/s41572-022-00370-w
|View full text |Cite
|
Sign up to set email alerts
|

Cough hypersensitivity and chronic cough

Abstract: Chronic cough is globally prevalent across all age groups. This disorder is challenging to treat because many pulmonary and extrapulmonary conditions can present with chronic cough, and cough can also be present without any identifiable underlying cause or be refractory to therapies that improve associated conditions. Most patients with chronic cough have cough hypersensitivity, which is characterized by increased neural responsivity to a range of stimuli that affect the airways and lungs, and other tissues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
127
3
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 162 publications
(140 citation statements)
references
References 249 publications
0
127
3
10
Order By: Relevance
“…We observed that current smokers were frequent among CC subjects in both community populations, which contrasted with the observations at specialist cough clinics where most are never or non-current smokers [31,38]. This might suggest a difference in CC patient characteristics between community and specialist cough clinics.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…We observed that current smokers were frequent among CC subjects in both community populations, which contrasted with the observations at specialist cough clinics where most are never or non-current smokers [31,38]. This might suggest a difference in CC patient characteristics between community and specialist cough clinics.…”
Section: Discussioncontrasting
confidence: 69%
“…Interestingly, unlike in South Korea, a male predominance (54.8%) was noted in CC patients in Taiwan, which is similar to those observed at specialist cough clinics in Guangzhou, China [ 30 ]. This might be attributed to ethnic or environmental factors distinct to Taiwan and Southeast China [ 31 ]. However, the present study was not designed to investigate the sex difference, and the findings warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…, the presence of active airway inflammation, mucus, or acid reflux triggering sensory nerves), (2) hyper-excitability in the cough reflex circuit, and (3) impaired cough inhibition. 82 Control of peripheral triggers may be achieved with optimal treatments according to current asthma guidelines. Treatment of patients with severe eosinophilic asthma, treatments with anti-IL-5 monoclonal antibody or OCS may help to relieve cough.…”
Section: The Concept Of Treatable Traits In Severe Asthmamentioning
confidence: 99%
“…on potential associated conditions, such as asthma, gastroesophageal reflux disease (GERD) and upper cough airway syndrome (formerly referred to as post-nasal drip syndrome) [7]. Guidelines on the management of IPF provide little in the way of recommendation for the treatment of cough.…”
mentioning
confidence: 99%